(untitled) (Historia, 2021)
When confronted with a media historiographical research project of vast scope, both in terms of period and subject, which approaches should the researcher take to ensure that the end result is a relatively "true reflection" of a given "past reality"? Which paradigms first need to be explored and understood before embarking on such a journey in order to stay focused, remain en route, and not lose one’s way in terms of a myriad of potential data, sources, approaches, processes, philosophies and theories? This article attempts to reflect on the writing of media history by visiting and unpacking some relevant paradigms and philosophies in order to find an applicable approach, an organising principle, or "road map", within the field of history/historiography, specifically media history/historiography, so as to be able to construct a history of a South African media company, the subject of the research project at hand. Gekonfronteer met ’n omvangryke mediahistoriografiese navorsingsprojek, beide in tydperk en onderwerp, watter benaderings kies die navorser om te verseker die eind resultaat is ’n relatiewe "ware weergawe" van ’n gegewe "verlede werklikheid"? Watter paradigmas moet eers ondersoek word voordat op so ’n reis vertrek word sodat die ondersoek gefokus en en route bly, om nie as ’t ware te verdwaal nie te midde van byna eindelose data, bronne, benaderings, prosesse, filosofieë en teorieë? Hierdie artikel probeer besin oor die skryf van mediageskiedenis deur verskeie relevante paradigmas en filosofieë te besoek in ’n poging om ’n toepaslike benadering, ’n organiserende beginsel, of "padkaart", binne die geskiedenis/historiografie, spesifiek mediageskiedenis/mediahistoriografie, te vind, in ’n poging om ’n geskiedenis van ’n Suid-Afrikaanse mediamaatskappy, die onderwerp van die studie, te konstrueer.